Respuesta :

(y-2) (x + 3) are factors of the xy + 3y-2x-6 form

Further explanation

Factoring is a statement of a form of addition into a multiplication

There are several factoring of the following forms:

  • 1. the forms ax + ay + az and ax + bx -cx

factoring:

ax + ay + az = a (x + y + z + ...)

ax + bx -cx = x (a + b-c)

  • 2. difference of two squares x²-y²

factoring:

x²-y² = (x-y) (x + y)

  • 3. the form x² + 2xy + y² and x²-2xy + y²

factoring:

x² + 2xy + y² = (x + y) (x + y) = (x + y)²

x²-2xy + y² = (x-y) (x-y) = (x-y)²

  • 4. form ax² + bx + c with a = 1

factoring:

 ax² + bx + c = (x + m) (x + n) with m x n = c and m + n = b

  • 5. the form ax² + bx + c with a ≠1 and a ≠0

factoring:

can be completed in 2 ways

a. distributive way

ax² + bx + c = ax² + px + qx + c with

p x q = a x c and

p + q = b

b. formula way

ax² + bx + c = 1/a (ax + m) (ax + n) with

m x n = a x c and

m + n = b

So from an addition form, for example:

ax + ay = a (x + y), then a and (x + y) are factors of the form ax + ay

So (y-2) (x + 3) are factors of the form xy + 3y-2x-6

Learn more

quadratic factoring equation

https://brainly.com/question/1580889

https://brainly.com/question/2278781

https://brainly.com/question/8991943

Keywords: factoring, quadratic equation, addition into a multiplication

Ver imagen ardni313
ACCESS MORE